Calculation method of 5G high-speed railway station spacing based on correlation analysis - Yan YANG; Tao ZHANG; Xirui GUO (Dianxin kexue)
A method of 5G cell station spacing for high-speed railways with simplified restriction conditions was presented that balance the gap between theoretical research and practical use.To begin, the influencing factors of 5G cell station spacing for high-speed railways were analyzed, such as incident angle, downtilt angle, station height, station gauge distance and coverage distance.Then, a simple station spacing calculation method was obtained with the restriction conditions simplified to a single parameter (coverage distance) by analyzing the correlation between available station height, gauge and coverage distance.Comparison and verification show that the cell station spacing calculation done with the proposed method has high accuracy, with a calculation error of only 3 m and an accuracy of 99.14%.